Raising the Enterprises' Environmental Performance by Taking Advantage of Business Process Modeling. (2015) - Fleaca, Elena; Fleaca, Bogdan; Negoita, Olivia; Danalache, Florin
Abstract: Tackling the environmental impact and the compliance with the environmental legislation have become critical challenges for Romanian enterprises. The paper is addressing the environmental protection and management concern by integrating different disciplinary components: environmental legislation aimed at preventing and reducing negative environmental impacts, engineering management aimed at designing the necessary systems for a coherent enterprises functioning, and IT as an efficiency tool for process modeling. The authors performed an empirical research by applying the business process modeling concept within the environmental protection domain taking advantage of the Simple BPM modeling application on the process of establishing environmental objectives. The results highlight that, regardless of industry, any enterprise acts in the green market segment has to remove the environmental management bottlenecks by designing and implementing effective management processes ease to use and correlated with the actual economic requirements.